A Quantitative Evaluation of Evidence-Based Beliefs and Implementation Among Community Pharmacists: Findings and Impact from United Arab Emirates - Jairoun, Ammar Abdulrahman; Al-Hemyari, Sabaa Saleh; Shahwan, Moyad; El-Dahiyat, Faris; Jairoun, Maimona; AL-Tamimi, Saleh Karamah; Mothana, Ramzi A; Khattab, Ahmed Husham (Risk management and healthcare policy, 2021)
The flux of pharmaceutical data can have a negative impact on the complexity of a pharmacist's decision-making process, which will demand an extensive evaluation from healthcare providers trying to choose the most suitable therapeutic plans for their patients. The current study aimed to assess the beliefs and implementations of community pharmacists in the UAE regarding evidence-based practice (EBP) and to explore the significant factors governing their EBP. Community pharmacies in Dubai and the Northern Emirates, UAE. A descriptive cross-sectional study was conducted over six months between December 2017 and June 2018. Community pharmacists who had three months' professional experience or more and were registered with one of three regulatory bodies (Ministry of Health, Health Authority Abu Dhabi, or Dubai Health Authority) were interviewed by three trained final-year pharmacy students. Face-to-face interviews were then carried out and a structured questionnaire was used. The average beliefs score was 36% (95% CI: [34%, 39%]) compared to an implementation score of 35% (95% CI: [33%, 37%]). A total of 505 subjects participated in the study and completed the entire questionnaire. On average, participants scored higher in beliefs score than implementation score. The results of the statistical modelling showed that younger, female, higher-position pharmacists with more experience and with low percentages of full-time working, and graduates from international/regional universities were more likely to believe in and implement the concept of EBP. A gap was identified between the beliefs and implementation of EBP. Developing educational EBP courses in undergraduate pharmacy curricula is of high importance, not only to increase knowledge levels but also to encourage commitment in those pharmacists to strive for professionalism and to support the provided patient care with evidence.